1994
DOI: 10.1161/01.cir.89.4.1632
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response of chronic beta-blocker treatment in heart failure from either idiopathic dilated or ischemic cardiomyopathy. Bucindolol Investigators.

Abstract: BACKGROUND Small-scale clinical investigations have demonstrated that single doses of beta-blocking agents can improve left ventricular function in heart failure from idiopathic dilated cardiomyopathy (IDC). The purpose of this multicenter clinical trial was to determine the dose-effect characteristics of beta-blockade in a heart failure population that includes ischemic dilated cardiomyopathy (ISCD). METHODS AND RESULTS Bucindolol is a nonselective bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
1
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(114 citation statements)
references
References 35 publications
2
107
1
4
Order By: Relevance
“…Xamoterol, an agent with partial agonist activity, improved clinical status, exercise capacity, and overall quality of life but significantly increased mortality in patients with congestive heart failure. 30 Bucindolol also had significant beneficial effects on quality of life [31][32][33][34][35][36] but failed to improve mortality in a long-term trial. 12 The reasons for the failure of the BEST trial are not clear, but several explanations have been considered, including the possibility that ␤-adrenergic blockade is not beneficial for all subsets of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Xamoterol, an agent with partial agonist activity, improved clinical status, exercise capacity, and overall quality of life but significantly increased mortality in patients with congestive heart failure. 30 Bucindolol also had significant beneficial effects on quality of life [31][32][33][34][35][36] but failed to improve mortality in a long-term trial. 12 The reasons for the failure of the BEST trial are not clear, but several explanations have been considered, including the possibility that ␤-adrenergic blockade is not beneficial for all subsets of patients.…”
Section: Discussionmentioning
confidence: 99%
“…70 Both compounds were well tolerated in mild-moderate (NYHA class II or III) heart failure. 66 -73 As would be expected by ␤-blocker effects on maximal heart rate, maximal exercise tolerance was not improved in the majority of these studies, 66,67,69,70 but several showed improvement or favorable trends in submaximal exercise. 67,70,72 …”
Section: Discovery Of Functional ␤ 2 -Ars On Cardiac Myocytes In Humamentioning
confidence: 91%
“…115 In addition, because of blunting of exercise heart rate the higher doses of ␤-blockers that are associated with the best reverse remodeling effects do not improve functional capacity. 69,74,75 Therefore, although it is clear that restoration of cardiac reserve accessible by high doses of ␤-agonists occurs when receptor signal transduction is restored by ␤-blocking agents, 47 improved ␤-AR signal transduction does not appear to account for reverse remodeling and does not result in improved functional capacity. One conceptual framework for the cause of heart failure is to simply ascribe it to altered myocardial gene expression.…”
Section: Mechanism Of Action Of ␤-Blockers Inmentioning
confidence: 99%
“…51 In that trial, this nonselective vasodilating compound was well tolerated, 51 in marked contrast to previous 2,3 and subsequent 69 experiences with the nonselective first-generation agent propranolol. The second multicenter trial performed with a ␤-blocking agent was the bucindolol multicenter trial, 81 which was a phase 2 dose-response trial designed to select a dose of bucindolol to be used in phase 3 trials (Table 3). This trial had primary end points of left ventricular function and exercise tolerance, with secondary end points of quality of life and mortality.…”
Section: Bucindololmentioning
confidence: 99%